1980
DOI: 10.1017/s0022172400027133
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella isolation with Rappaport's medium after pre-enrichment in buffered peptone water using a series of inoculum ratios

Abstract: The ability of malachite green/magnesium chloride broth (Rappaport's medium) to isolate salmonellas from 25 ml quantities of sewage-polluted natural water was investigated. Samples were first pre-enriched in buffered peptone water and varying volumes of inoculum from the pre-enrichment culture were inoculated into Rappaport's broth. Inoculum ratios in the range 1:2000 to 1:10 were examined. The inoculum ratio denotes the ratio of the volume of inoculum to the volume of fluid medium into which it is introduced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…(Tables 2 and 3.) This observation confirms the data reported by Harvey et al (1979) and Harvey & Price (1980, 1982b. These authors have shown Total positive samples by at least one enrichment procedure: 111 (27-1 %).…”
Section: Resultssupporting
confidence: 93%
“…(Tables 2 and 3.) This observation confirms the data reported by Harvey et al (1979) and Harvey & Price (1980, 1982b. These authors have shown Total positive samples by at least one enrichment procedure: 111 (27-1 %).…”
Section: Resultssupporting
confidence: 93%
“…The magnesium chloride, malachite green medium was the most successful of the three enrichment broths for the isolation of salmonellas in this study ( (90) 187 (89) 197 (94) 210 (100) Rappaport's medium must be used with a high inoculum ratio (Jameson, 1963;Harvey & Price, 1980). This term denotes the ratio of the volume of inoculum to the volume of the medium into which it is introduced.…”
Section: Resultsmentioning
confidence: 97%
“…The importance of inoculation ratios in the isolation of salmonellae has been demonstrated by many workers (Jameson, 1961;1963;Harvey & Price, 1980;Fricker, 1984a) and a ratio of 1: 100 has been recommended for RV medium (Vassiliadis, 1983). In this study, an inoculation ratio of 1: 100 was shown to be superior to 1:20, 1:50, 1:200 and 1: 1000 for isolating salmonellae from chicken giblets after pre-enrichment in buffered peptone water, for all three formulations of Rappaport's medium used.…”
Section: Discussionmentioning
confidence: 97%